Decomposition of tetrafluorocarbon in dielectric barrier discharge reactor - Na, BK; Choi, JW; Lee, H; Song, HK (KOREAN INST CHEM ENGINEERS, 2002)
The decomposition of CF4 in dielectric barrier discharge at atmospheric pressure was examined. The effect of O-2 contents, N-2 contents, and total flow rate on CF4 conversion was experimentally investigated. The maximum conversion of CF4 was about 87% at 5 kV, 15 kHz for the feed gas stream containing 5 sccm CF4, 7.5 SCCM O-2, and 187.5 sccm Ar. CO, CO2, and COF2 were the main products when O-2 was used as the additive gas. NOx was produced when N-2 was used as the additive gas. The conversion of CF4 was increased while the applied voltage and the residence time were increased. When nitrogen was added to argon as the diluent gas, the conversion of CF4 was decreased with the increase of the nitrogen content.
Keywords: PLASMA REACTOR; ABATEMENT; CONVERSION; METHANE; HYDROCARBONS; GAS